Treatment of oroantral fistula: case report - Ferreira, Kétsia Rayssa Henriques; Moraes, Josiclei de Castro; Meira, Clarina Louis Silva; Souza, Lucas Lacerda de; Conte Neto, Nicolau; Xavier, Thiago Brito (Journal of Oral Diagnosis, 2021)
The oroantral fistula is a pathological communication between the oral cavity and the maxillary sinus that is covered with epithelial tissue from both sites. It may be caused by dental infections, surgical iatrogenesis, radiotherapy or trauma. To avoid contamination of the maxillary antrum, this connection must be closed. Several tissue flaps may be used for this. The aim of this paper is to present a case of oroantral fistula treatment in the posterior region of the left maxilla using a vestibular sliding strip flap with palatal inter- position. A 54-year-old female patient was presented with an oroantral fistula confirmed by the Valsalva maneuver and radiographic examination. The patient was previously ex- posed to antimicrobial treatment in order to solve the acute infectious disease, which was accompanied by surgical closure. Dehiscence and drainage via fistula in the postoperative period motivated the performance of a second surgical procedure using a sliding vestibular flap with palatal interposition. It is concluded that infection prevention is important for the effectiveness of treatment, as well as patient’s cooperation in the postoperative period.